Metformin: The Winding Path from Understanding Its Molecular Mechanisms to Proving Therapeutic Benefits in Neurodegenerative Disorders - Laura Mihaela Isop; Andrea Elena Neculau; Radu Dan Necula; Cristian Kakucs; Marius Alexandru Moga; Lorena Dima (MDPI AG, 2023)
Metformin, a widely prescribed medication for type 2 diabetes, has garnered increasing attention for its potential neuroprotective properties due to the growing demand for treatments for Alzheimer's, Parkinson's, and motor neuron diseases. This review synthesizes experimental and clinical studies on metformin's mechanisms of action and potential therapeutic benefits for neurodegenerative disorders. A comprehensive search of electronic databases, including PubMed, MEDLINE, Embase, and Cochrane library, focused on key phrases such as "metformin", "neuroprotection", and "neurodegenerative diseases", with data up to September 2023. Recent research on metformin's glucoregulatory mechanisms reveals new molecular targets, including the activation of the LKB1-AMPK signaling pathway, which is crucial for chronic administration of metformin. The pleiotropic impact may involve other stress kinases that are acutely activated. The precise role of respiratory chain complexes (I and IV), of the mitochondrial targets, or of the lysosomes in metformin effects remains to be established by further research. Research on extrahepatic targets like the gut and microbiota, as well as its antioxidant and immunomodulatory properties, is crucial for understanding neurodegenerative disorders. Experimental data on animal models shows promising results, but clinical studies are inconclusive. Understanding the molecular targets and mechanisms of its effects could help design clinical trials to explore and, hopefully, prove its therapeutic effects in neurodegenerative conditions.